Rancang Bangun Pembangkit Listrik Tenaga Surya Polycristalline Dilengkapi Lapisan Antiglare - TRIYADI, ARIF RIZKI; KRISTIYADI, TARSISIUS (e-Proceeding FTI, 2024)
Antiglare coating is a layer that serves to reduce reflections and increase light absorption in solar cells so that they can improve their performance. Anti-reflection properties can be obtained by modifying the surface by giving a texture to the surface. With this method, the light available for PV conversion can be increased so that the performance of solar cells can be increased. The reflection loss in the solar cell system is 2.9% due to the glass material in the solar cell, with the addition of an antiglare layer it can increase performance by 14%. In the test results before using antiglare, the highest power was found on the second day of testing, which was 49.504 Watt with a charging voltage of 20.8 Volts and a charging current of 2.38 Amperes when the light intensity was 1146 W/m2 with an efficiency of 11.93953%. In the test results using antiglare, the highest power is found on the first day of testing, which is 49.796 Watt with a charging voltage of 21.1 Volts and a charging current of 2.36 Ampere when the light intensity is 1152 W/m2 with an efficiency of 11.9474%. Abstrak Lapisan antiglare adalah lapisan yang berfungsi untuk mengurangi refleksi dan meningkatkan penyerapan cahaya pada sel surya sehingga dapat meningkatkan kinerjanya. Sifat anti refleksi dapat diperoleh dengan cara memodifikasi permukaan dengan memberikan tekstur pada permukaannya. Dengan metode ini, cahaya yang tersedia untuk konversi PV dapat ditingkatkan sehingga kinerja sel surya pun dapat meningkat. Rugi refleksi pada sistem sel surya sebesar 2,9 % disebabkan bahan glass pada sel surya, dengan penambahan lapisan antiglare dapat meningkatkan performance sebesar 14 %. Pada hasil pengujian sebelum menggunakan antiglare, daya tertinggi terdapat pada pengujian hari kedua, yaitu 49,504 Watt dengan tegangan pengisian 20,8 Volt dan arus pengisian 2,38 Ampere saat intensitas cahaya 1146 W/m2 dengan efisiensi 11,93953%. Pada hasil pengujian dengan menggunakan antiglare, daya tertinggi terdapat pada pengujian hari pertama, yaitu 49,796 Watt dengan tegangan pengisian 21,1 Volt dan arus pengisian 2,36 Ampere saat intensitas cahaya 1152 W/m2 dengan efisiensi 11,9474%.